1977
DOI: 10.1037/0022-3514.35.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Do people use consensus information in making causal attributions?

Abstract: Nisbett and Borgida's failure to obtain effects for consensus information on person versus situation attributions was questioned regarding their operationalization of consensus. Nisbett and Borgida's finding was replicated, but an operationalization of consensus designed to reflect Kelley's conceptual criterion of perceived covariation and to represent more levels of consensus resulted in significant consensus effects on person versus situation attributions In Study 2, consensus information was found to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
4

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 13 publications
5
130
4
Order By: Relevance
“…We show that (a) our , Experiment 2) findings contradict the predictions made by the linear-combination rules and Suppes's (1984) model, (b) the differing results reported by Nisbett and Borgida (1975) and Wells and Harvey (1977) in their controversial debate regarding the use of consensus information are both consistent with our model, and (c) the differing attributions of actors and observers are also consistent with our model.…”
Section: Discussionsupporting
confidence: 60%
“…We show that (a) our , Experiment 2) findings contradict the predictions made by the linear-combination rules and Suppes's (1984) model, (b) the differing results reported by Nisbett and Borgida (1975) and Wells and Harvey (1977) in their controversial debate regarding the use of consensus information are both consistent with our model, and (c) the differing attributions of actors and observers are also consistent with our model.…”
Section: Discussionsupporting
confidence: 60%
“…The observed differential use of consensus information is of particular interest in the case of self-predictions. Several studies have found previously that consensus information affects judgments of others but not of one's own behavior (e.g., Hansen & Donoghue, 1977;Wells & Harvey, 1977). The present study indicates that judgements of one's own behavior can be infiuenced by consensus information, and this may be particularly true for certain people (viz., high self-monitors).…”
Section: Discussionmentioning
confidence: 58%
“…Research is available to support the contention that narrative messages are significantly more memorable and persuasive than are statistical/logical arguments (Borgida & Nisbett, 1977;Kazoleas, 1993;Koballa, 1986;Nisbett & Ross, 1980;Taylor & Thompson, 1982). However, other research indicates that fact-based and statistical evidence is more persuasive than personal narratives (see Allen & Preiss, 1997, for results of their metaanalysis; Baesler & Burgoon, 1994;Dickson, 1982;Wells & Harvey, 1977). Furthermore, still other evidence exists indicating that there is no difference in the persuasiveness of these different message types (Iyengar & Kinder, 1987;Nadler, 1983;Reyna, Woodruff, & Brainerd, 1987).…”
Section: Fear Appeals and The Testicular Self-exam Mormanmentioning
confidence: 86%